(untitled) (Architecture Image Studies, 2026)
With the growing trend of online short-form content consumption, the creation and adoption of short-form dramas are similarly on the rise. The user base for these dramas has witnessed a notable increase, particularly in Asia and North America. Given this rapid expansion, their global market impact is anticipated to be substantial. Building upon an extended Technology Acceptance Model (TAM), this study conceptualized users’ perceptions by integrating individual and social characteristics to construct a comprehensive research model predicting user attitudes and continuous usage intentions. Data were collected via an online survey administered to short-form drama users to assess their perceptions, attitudes, and intentions regarding the continued use of short-form dramas. The survey results revealed that Perceived Usefulness, Perceived Ease of Use, and Perceived Playfulness of short-form dramas positively influenced user attitudes. Furthermore, these attitudes were found to have a significant positive effect on continued use intentions. This study contributes to a more comprehensive understanding of short-form drama consumption, offering valuable insights into user behavior for drama production teams and related marketers.